Studies on shipping fever and shipping shrink in cattle - Anthony, H.D.; Kelley, D.C.; Nelson, D.L.; Smith, E.F.; Wearden, S.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is the second year in which an attempt was made to determine some basic facts related to shipping fever and shipping shrink in weaned stocker calves. As in the previous years, the calves used in this study were from Jeff Ranch, Fort Davis, Texas. They were gathered early October 21, 1960, weaned from the cows, loaded into trucks, and transported 50 miles to loading pens in Alpine, Texas.
Keywords: Beef; Shipping fever; Shipping shrink